An integrated program with home blood-pressure monitoring and village health volunteers for treating poorly controlled hypertension at the primary care level in an urban community of Thailand - Visanuyothin S; Plianbangchang S; Somrongthong R (Dove Medical Press, 2018)
Sawitree Visanuyothin,1,2 Samlee Plianbangchang,1 Ratana Somrongthong1 1College of Public Health Sciences, Chulalongkorn University, Bangkok, Thailand; 2Social Medicine Department, Maharat Nakhon Ratchasima Hospital, Nakhon Ratchasima, Thailand Purpose: Hypertension (HT) is accountable for death in half of the patients suffering from heart disease and stroke. Many treatment strategies have been used, but little research exists on an integrated program with home blood pressure monitoring (HBPM) and village health volunteers (VHVs) in an urban area of Thailand. The present study aims to determine the effectiveness of the integrated program, HBPM, and VHVs in supporting the target population. Patients and methods: This quasi-experiment was conducted from July to November 2017. Patients with poorly controlled HT were randomly selected from each of the two primary care units in Nakhon Ratchasima, Thailand. The participants were separated into an experiment (n=63) and control group (n=65). The experiment group participated in the integrated program, which was based on the 20-item Health Literate Care Model. A valid and reliable questionnaire was used to collect data from participant interviews. Blood-pressure monitoring was used to measure systolic home blood pressure and diastolic home blood pressure. Descriptive statistics, chi-squared tests, Fisher’s exact test, the independent t-test, and the Wilcoxon–Mann–Whitney test were used to compare the baseline data. Multiple logistic regression was used to compare the differences between the mean changes in the outcomes. Results: At the end of the 3-month follow-up appointment, significant statistical changes were found. Systolic home blood pressure, diastolic home blood pressure, and body mass index changed −4.61 (95% CI −8.32, −0.90) mmHg (P-value=0.015), −3.5 (95% CI −5.31, −1.72) mmHg (P-value <0.001), and −0.86 (95% CI −1.29, −042) (P-value <0.001) respectively. Participant scores in lifestyle and management knowledge, and self-management behaviors significantly increased by 0.76 (95% CI 0.15–1.38) point (P-value=0.016) and 0.15 (95% CI 0.06, 0.24) point (P-value=0.001), respectively. Conclusion: The integrated program, HBPM, and VHVs were effective in decreasing blood pressure and body mass index, and increasing knowledge and self-management behaviors among urban patients with poorly controlled HT. Keywords: self-management behaviors, lifestyle and management knowledge, health literacy of chronic diseases, adherence of hypertension patients